Design and analysis of low-complexity terahertz receiver - Sharma V.; Sharma S.; Bhatia V. (My University, 2025)
Terahertz (THz) band communication is considered as a promising technology for 6G wireless technology due to availability of large bandwidth at THz bands. Most receivers for symbol detection need channel state information (CSI), however estimating CSI is complex for THz bands. Hence, in this paper, we design and analyze low complexity THz receiver without considering the CSI for symbol detection. The rate adaptation for THz communication systems is also analysed for the distance attenuation. Since, at THz the performance is sensitive to distance. We consider modified transmitted-reference (MTR) pulsed and optimal lth-order energy detector (OED) based THz communication system. Simulations are carried out to show effectiveness of MTR and OED for pulse-based THz band wireless systems by considering the effect of distance, data rate, and absorption by molecular gases. © 2020 IEEE.